Awareness, knowledge and practice of contact lens use among medical students - Thiraviam, Mahima; Kumaresan, Vinisha; P., Anuradha (International Journal of Research in Medical Sciences, 2022)
Background: Contact lens are thin optical lenses that are commonly used for correcting refractive errors. They are available in various materials, types, and colors. The complications associated with contact lens usage are allergic conjunctivitis, keratitis, and neovascularization. These complications arise with a lack of proper practice and knowledge about contact lens. In our study, we assess the awareness, knowledge, and practice of contact lens use among medical students of Saveetha medical college and hospital. Study design was cross-sectional study. Place of study was Saveetha medical college and hospital, Thandalam, Chennai. Methods: A cross-sectional study was conducted on contact lens users among medical students. A total of 100 contact lens users participated in the study of which 70 were females and 30 were males. The study was done using pretested semi-structured questionnaire. The data were collected, tabulated, and analyzed using SPSS version 25 software. Result: There is a female predominance with about 70%. Most of the participants use contact lens for both cosmetic and refractive errors. About 91% of students use soft contact lens. Nearly 70% of students are not aware of overwear syndrome. Problems faced by contact lens wearers include dryness, eye discomfort, pain, watering, and redness. Conclusions: The lack of proper practice, knowledge, and awareness of contact lens use even in those knowledgeable like medical students increases the risk of complications. Thus, there is a need to provide more education to consumers.